Potential health benefits from coffee consumption - Michał Perszke; Dominika Egierska (Journal of Education, Health and Sport, 2022)
The history of coffee goes back to the 10th century. Currently, coffee is a widespread drink, with recent studies reporting a global consumption of 164,9 million 60-kg bags in 2020/2021. The effect of coffee on human health has been studied for many years. The active ingredients of coffee include polyphenols, lactones, diterpenes, niacin, the trigonelline (vitamin B3 precursor), magnesium and potassium. Potential factors that could change its properties include the type of beans, the roasting process, the grinding process and the brewing process. Authors searched PubMed and Google Scholar using searchterms coffee, cardiovascular system disease, CVD, type II diabetes, Alzheimer’s disease and caffeine. We manually searched the references of selected articles for additional relevant articles. We selected articles relevant to a general medicine readership, prioritizing systematic reviews, cases and clinical practice guidelines. The literature contains the latest reports on the impact of coffee on human health, including cardiovascular diseases, type II diabetes and Alzheimer’s disease. Drinking coffee may reduce the risk of cardiovascular disease, because of the caffeine blocking A1 and A2A receptors. It may also contribute to decreasing the risk of type II diabetes, increasing the secretion of GLP-1 and increasing the sensitivity of tissues to insulin. The influence of coffee on the development of Alzheimer’s disease is still being investigated. Coffee is a common drink for many people, so you should know its impact on human health. Contrary to appearances, coffee may have many health-promoting properties.